Surface‐Dependent Properties and Tunable Photodetection of CsPbBr3 Microcrystals Grown on Functional Substrates (Advanced Optical Materials 3/2022). Issue 3 (5th February 2022) - Abiedh, Khouloud; Dhanabalan, Balaji; Kutkan, Seda; Lauciello, Simone; Pasquale, Lea; Toma, Andrea; Salerno, Marco; Arciniegas, Milena P.; Hassen, Fredj; Krahne, Roman
Abstract : In article number 2101807, Roman Krahne and co‐workers introduce a simple and low‐cost fabrication method to grow metal halide perovskite microcrystals directly on functional substrates. The microcrystals feature a pyramidal cavity on their top surface that provides advantageous optoelectronic properties, since its facets lead to enhanced light emission and improved electrical contact formation. Photodetectors built from single microcrystals on conductive substrates demonstrate excellent responsivity and detectivity in the visible range and can work either in broad and narrow band detection.